Acute Complications of Myocardial Infarction in the Current Era: Diagnosis and Management. Issue 7 (October 2015) - Bajaj, Anurag; Sethi, Ankur; Rathor, Parul; Suppogu, Nissi; Sethi, Arjinder
Abstract : Abstract: Coronary heart disease is a major cause of mortality and morbidity worldwide. The incidence of mechanical complications of acute myocardial infarction (AMI) has gone down to less than 1% since the advent of percutaneous coronary intervention, but although mortality resulting from AMI has gone down in recent years, the burden remains high. Mechanical complications of AMI include cardiogenic shock, free wall rupture, ventricular septal rupture, acute mitral regurgitation, and right ventricular infarction. Detailed knowledge of the complications and their risk factors can help clinicians in making an early diagnosis. Prompt diagnosis with appropriate medical therapy and timely surgical intervention are necessary for favorable outcomes.